Assessment of chemical composition and in vitro rumen fermentation of tuber and crop peels - Samsudin, A.A.; Muhammad, A.I.; Sani, N. I. M; Zainuddin, N.N.; Hemly, N. I. M; Khairul, A.B. (Malaysian Society of Animal Production, 2024)
Tuber and root crops, rich in carbohydrates, are staple foods in Malaysia. However, their peels, often discarded, represent a potential feed resource for ruminants. This study assessed the nutritive value and in vitro gas production of various root and tuber crop peels as a sustainable feed ingredient for ruminant livestock. The root and tuber peels used in this experiment were potato peels (T1), taro peels (T2), sweet potato peels (T3), cassava peels (T4) and Chinese yam peels (T5). The proximate analysis (moisture, dry matter (DM), organic matter (OM), crude protein (CP), crude fibre (CF), neutral detergent fibre (NDF), acid detergent fibre (ADF) and acid detergent lignin (ADL)) was conducted on the peels samples to evaluate their nutritional profiles. The results showed that potato peels showed the highest (P < 0.05) moisture, CF, NDF, and ADL contents compared to other root and tuber peels. Conversely, taro peels showed the highest CP, ADF, and ADL contents. Cassava peels had the highest DM and ash contents. Significant (P < 0.05) differences were observed in the metabolisable energy (ME) content, estimated based on digestible dry matter (DDM) content, among the various root and tuber peels. The ME content of Chinese yam peels was higher than that of other root and tuber peels. At the 4th, 6th, 8th, 10th, 12th, 24th, and 72nd hours of incubation, there was a significant (P < 0.05) difference in the gas produced by different peels in the in vitro rumen fermentation analysis. The taro peels produced the least gas, while Chinese yam produced the highest. In conclusion, cassava and Chinese peels could improve rumen fermentation efficiency based on their DM and ME content in terms of in vitro gas production.